2019
DOI: 10.1293/tox.2018-0049
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl fumarate ameliorates cisplatin-induced renal tubulointerstitial lesions

Abstract: Dimethyl fumarate (DMF) has an antioxidant effect by activating the nuclear factor erythroid 2-related transcription factor 2 (Nrf2). Cisplatin (CIS) has nephrotoxicity as a frequently associated side effect that is mainly mediated by oxidative stress. In this study, we investigated whether the DMF-mediated antioxidative mechanism activated by Nrf2 can ameliorate CIS-induced renal tubulointerstitial lesions in rats. In Experiments 1 and 2, 25 five-week-old male Wistar rats were divided into five groups: contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…SA and cisplatin-treated rats showed elevation in these key antioxidants indicating an enhanced antioxidant defense system following SA treatment [ 103 ]. Pharmacologically, it has been demonstrated that activation of the Nrf2 signaling pathway by N,N-dimethylformamide (DMF) following cisplatin treatment attenuated AKI [ 102 ], as well as tubulointerstitial lesions [ 106 ]. Both ameliorating effects are associated with stimulation of antioxidants such as HO-1 and NAD(P)H quinone oxidoreductase 1 (NQO1) [ 102 , 106 ].…”
Section: Interventions Targeting Molecular Mechanisms Ciakimentioning
confidence: 99%
See 1 more Smart Citation
“…SA and cisplatin-treated rats showed elevation in these key antioxidants indicating an enhanced antioxidant defense system following SA treatment [ 103 ]. Pharmacologically, it has been demonstrated that activation of the Nrf2 signaling pathway by N,N-dimethylformamide (DMF) following cisplatin treatment attenuated AKI [ 102 ], as well as tubulointerstitial lesions [ 106 ]. Both ameliorating effects are associated with stimulation of antioxidants such as HO-1 and NAD(P)H quinone oxidoreductase 1 (NQO1) [ 102 , 106 ].…”
Section: Interventions Targeting Molecular Mechanisms Ciakimentioning
confidence: 99%
“…Pharmacologically, it has been demonstrated that activation of the Nrf2 signaling pathway by N,N-dimethylformamide (DMF) following cisplatin treatment attenuated AKI [ 102 ], as well as tubulointerstitial lesions [ 106 ]. Both ameliorating effects are associated with stimulation of antioxidants such as HO-1 and NAD(P)H quinone oxidoreductase 1 (NQO1) [ 102 , 106 ]. Stimulation of these two antioxidants was observed in mice treated with Isoorientin a flavone, suggested to activate the Nrf2 signaling cascade [ 44 ].…”
Section: Interventions Targeting Molecular Mechanisms Ciakimentioning
confidence: 99%
“…In addition, fumarate seems to have protective effects in the kidney, as demonstrated in kidney damage induced by ciclosporin, cisplatin, folic acid, and I/R [ 143 , 144 , 145 ], in which dimethyl fumarate administration reduce kidney damage by enhancing the antioxidant response driven by Nrf2 ( Figure 2 g). Moreover, dimethyl fumarate is already approved by the food and drug administration (FDA) as an immunomodulatory drug for the therapeutic management of multiple sclerosis [ 146 ].…”
Section: Fumaratementioning
confidence: 99%
“…Bardoxolone reduced fibrosis through the Nrf2/Smad7 axis, inhibiting the TGF-β/Smad signaling, and ameliorating aristolochic acid-induced AKI [ 183 ]. In cisplatin-AKI, DMF also reduced peritubular fibrosis [ 184 ]. In a mouse model of folic acid-induced AKI, specific deletion of GSK3β in renal tubules or treatment with a GSK3β inhibitor improved the Nrf2 antioxidant response, independently of Keap1, protecting from AKI to CKD transition [ 185 ].…”
Section: Nrf2 and Akimentioning
confidence: 99%